Characterization and comparison of fluoroelastomer unfilled, filled with carbon nanotube (unmodified, acid or base surface modified) and carbon black using TGA-GCMS. (November 2021) - Heidarian, J; Hassan, A
Carbon nanotube (CNT)-, surface-modified CNT: acid (–COOH) modified (MCNT) or base (–OH) modified (OHCNT), carbon black (CB)-filled fluoroelastomer (FE) and unfilled FE were prepared (CNT/FE, MCNT/FE, OHCNT/FE, CB/FE and FE). The thermal properties of the composites were assessed by TGA-GCMS and TGA and compared for all samples. TGA-GCMS results show that degradation products that obtained due to breakage of the CF2 -CH2 bond (group A) and CF2 -CF2 bond (group B) in base FE, obtained in lower temperatures and higher temperatures of TGA scan respectively, therefore CF2 -CF2 bond is more thermally stable than CF2 -CH2 . For degradation products of group A and group B, the relative abundance decreased in the following orders respectively for all samples: CB/FE, CNT/FE, OHCNT/FE, FE, MCNT/FE; and MCNT/FE, OHCNT/FE, FE, CNT/FE, CB/FE. Therefore nanofillers and particularly surface-modified nanofillers produce less amount of group A degradation products and more amount of group B degradation products and therefore increase the thermal stability of the base FE. For all samples, the volatile degradation products that have the highest intensity are: (C6 F7 H2 ) +, C4 H6 F + and C6 F11 + and the volatile degradation products are similar except for OHCNT/FE and MCNT/FE. TGA results also show that thermal stability reduced in the following orders in the lower temperature range and higher temperature range respectively: OHCNT/FE, FE, CB/FE, CNT/FE, MCNT/FE; and CB/FE, MCNT/FE, CNT/FE, FE, OHCNT/FE. Totally the results show that OHCNT/FE, MCNT/FE and CNT/FE can be used at high temperatures for making O-rings for very deep oil and gas drilling.